Role of the right temporoparietal junction in intergroup bias in trust decisions. Issue 6 (19th December 2019) - Fujino, Junya; Tei, Shisei; Itahashi, Takashi; Aoki, Yuta Y.; Ohta, Haruhisa; Kubota, Manabu; Hashimoto, Ryu‐ichiro; Takahashi, Hidehiko; Kato, Nobumasa; Nakamura, Motoaki
Abstract: Intergroup bias, which is the tendency to behave more positively toward an in‐group member than toward an out‐group member, is pervasive in real life. In particular, intergroup bias in trust decisions substantially influences multiple areas of life and thus better understanding of this tendency can provide significant insights into human social behavior. Although previous functional magnetic resonance imaging studies showed the involvement of the right temporoparietal junction (TPJ) in intergroup trust bias, a causal relationship between the two has rarely been explored. By combining repetitive transcranial magnetic stimulation and a newly developed trust game task, we investigated the causal role of the right TPJ in intergroup bias in trust decisions. In the trust game task, the counterpart's group membership (in‐group or out‐group) and reciprocity were manipulated. We applied either neuronavigated inhibitory continuous theta burst stimulation (cTBS) or sham stimulation over the right TPJ before performing the trust game task in healthy volunteers. After the sham stimulation, the participants' degrees of investments with in‐group members were significantly higher than those with out‐group members. However, after cTBS to the right TPJ, this difference was not observed. The current results extend previous findings by showing that the causal roles of the right TPJ can be observed in intergroup bias in trust decisions. Our findings add to our understanding of the mechanisms of human social behavior.